2022
DOI: 10.3390/agronomy12112648
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Protoplasts-Based Transient Expression System in Banana (Musa spp.)

Abstract: The breeding of triploid banana cultivars with improved traits, such as yield and disease resistance, remains a major challenge for breeders. One reason is that the molecular study and functional gene analysis in bananas fall behind due to the difficulties of its genetic manipulation. The plant protoplast-based transient transformation has been documented and widely used as a versatile and convenient system for functional gene analysis in many plant species. However, an efficient high-quality protoplast isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The results in holm oak showed that the best transfection efficiency (62%) was achieved with 10 µg of plasmid and with GFP expression recorded 24h from the transfection process. By contrast, in Liriodendron ( Huo et al., 2017 ) and banana ( Zhao et al., 2022 ) the highest values were attained with 20 μg. Finally, our transfection values were higher than those previously obtained with protoplasts of European chestnut tree ( Pavese et al., 2022 ) and Cymbidium Orchids ( Ren et al., 2020 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results in holm oak showed that the best transfection efficiency (62%) was achieved with 10 µg of plasmid and with GFP expression recorded 24h from the transfection process. By contrast, in Liriodendron ( Huo et al., 2017 ) and banana ( Zhao et al., 2022 ) the highest values were attained with 20 μg. Finally, our transfection values were higher than those previously obtained with protoplasts of European chestnut tree ( Pavese et al., 2022 ) and Cymbidium Orchids ( Ren et al., 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…DNA transfection can be performed by PEG, electroporation, particle bombardment, and DNA microinjection, however, the use of PEG-mediated transient editing showed higher transfection efficiency and it is cost-effective and simple in terms of releasing RNPs into the protoplasts ( Shen et al., 2014 ; Subburaj et al., 2022 ). PEG has been applied to transfect protoplasts of many different plant species including woody species such as poplar ( Tan et al., 2013 ), Liriodendron ( Huo et al., 2017 ), European chestnut ( Pavese et al., 2022 ) and banana ( Zhao et al., 2022 ). The protoplast to plasmid DNA ratio is an essential factor influencing transfection efficiency ( Burris et al., 2016 ), and generally the amount of plasmid DNA to be used is between 10 to 20 μg ( Huo et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Porphyrin metabolism provides the vital pigments for chlorophyll and heme [ 34 ]. Its biosynthesis begins with the formation of 5-aminolevulinic acid (ALA) as the first step [ 35 ]. The study examined the porphyrin metabolism characters in the PT and WT of Ananas comosus var.…”
Section: Resultsmentioning
confidence: 99%
“…Protoplast transformation systems can be applied in studies on cell signaling pathways in response to hormones [7], immediate transcriptome responses, and regulatory networks [8]. Protoplast-based biochemical and molecular studies have been applied to carnations [9], cotton [10], citruses [11], eggplants [7], oil palms [12], pineapples [13], Mangifera indica L. [14], bananas [15], etc. This is because the versatility and ability of protoplast transient expression systems can be developed and applied to many non-model plants that have transformation platforms that are difficult to use [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the cellulase R-10 degrades natural cellulose and dissolves plant cell walls [23], the macerozyme R-10 contains pectinase and hemicellulose that degrade the plant tissues to single cells [24], and the mannitol provides a suitable osmotic pressure and thereby ensures the integrity of the protoplasts [25]. Moreover, the digestion time affects the protoplast yield, and prolonging the digestion time may or may not increase the protoplast yield because an extended digestion time may result in protoplast breakage [15]. The isolated protoplast potency and viability rate are dependent on the digestion solution's pH value.…”
Section: Introductionmentioning
confidence: 99%